A Geometry of Specialization - Joseph F. Francois; Douglas Nelson (Tinbergen Institute, 1998)
Division of labor models have become a standard analytical tool, along withcompetitive general equilibrium models (Ricardian, HOS, Ricardo-Viner), in public finance, trade, growth, development, and macroeconomics. Yet unlike the earlier models, specialization models lack a canonical representation. This is because they are both new and complex, characterized by multiple equilibria, instability, and emergent structural properties under parameter transformation. We develop a general framework for such models, illustrating results from current research on specialization models, and explaining why one sub-class of these models is particularly difficult to illustrate easily.
Keywords: F12; O12; O41; 330; specialization; trade and development; location of industry; agglomeration; Außenwirtschaftstheorie; Internationale Arbeitsteilung; Theorie